Application Programming Interface (API) with Representational State Transfer (REST) for Balinese Traditional Song Semantic Ontology - Suryana, Kadek Andre; Raharja, Made Agung; Pramartha, Cokorda (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Technological developments and the era of globalization greatly affect the development of cultural heritage. One of the local cultural heritages in Bali is the Balinese song. Balinese songs are commonly used in traditional ceremonies or sung by children. In this study, the author uses semantic ontology technology to store knowledge in the form of a knowledge graph which will then be accessed through a query process to the Apache Jena Fuseki with a SPARQL query. This research succeeded in developing microservices in the form of a REST API to help receive and send requests properly. The REST API that has been created has successfully passed the test scenarios that have been carried out in this research.